PENGARUH PAD, DANA PERIMBANGAN, DAN PEMBIAYAAN TERHADAP BELANJA DAERAH SERTA DETEKSI FLYPAPER EFFECT DI INDONESIA - Try Firda Rahmasari (2023)
The granting of authority on the basis of regional autonomy should be able to gained regional independence to manage their Local Own-source Revenue. However, there are still many previous studies found the flypaper effect phenomenon in Indonesia. This study aims to determine the effect of Local Own-source Revenue, Balancing Funds, and Local Government Financing on Regional Expenditures and to detect the flypaper effect phenomenon of the district/city in Indonesia. This research method is quantitative which use purposive sampling and obtained 467 districts/cities in Indonesia in 2021 fiscal year. The hypothesis testing in this study uses multiple linear regression analysis using STATA program with a significance level 5%. The results show that Local Own-source Revenue, General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund have no significant effect on Regional Expenditures and Local Government Financing have positive effect on Regional Expenditures. Furthermore, there is no flypaper effect was found in districts/cities in Indonesia, but other funding mechanisms were found from Local Government Financing. Keywords: Flypaper Effect, Local Own-source Revenue, Balancing Funds, Local Government Financing, Regional Expenditures